1998
DOI: 10.1039/a705704k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of simple alcohols on Fe2O3powders An XPS and FTIR study

Abstract: he interaction between powders and methanol, ethanol, propan-1-ol and butan-1-ol has been studied by means of a-Fe 2 O 3 FTIR and XPS. Mass spectrometry has been used to characterise the volatile products. Methanol is chemisorbed mainly dissociatively whereas molecular chemisorption is prevalent in higher alcohols. When methanol is chemisorbed, heating induces the formation of formate (at temperatures [400 K) while hydrocarbons are the main products (at temperatures [500 K) of the other alcohols. Consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 7 publications
3
53
0
Order By: Relevance
“…As shown in Fig. 11A, the Fe 2p peak of fresh catalyst had only one signal at 710.2 eV, which corresponds to Fe 2 O 3 [45,46]. In the characteristic chloride region of this catalyst, no signal was observed.…”
Section: Characterization Of Iron Speciesmentioning
confidence: 84%
“…As shown in Fig. 11A, the Fe 2p peak of fresh catalyst had only one signal at 710.2 eV, which corresponds to Fe 2 O 3 [45,46]. In the characteristic chloride region of this catalyst, no signal was observed.…”
Section: Characterization Of Iron Speciesmentioning
confidence: 84%
“…In direct methanol fuel cell applications, electrolytes are under constant exposure to methanol fuel. Methanol can be adsorbed on metal oxide surfaces by molecular physisorption and dissociative chemisorption [38][39][40]. Although the adsorption strength of methanol on metal oxide was found to be smaller than acetic acid [40], it would be interesting for future studies to understand the effect of methanol adsorption and methanol concentration on protonic conductivity of metal oxides.…”
Section: Proton Conductivitymentioning
confidence: 96%
“…By taking into account the reactivity studies here reported and literature data, we can suppose that alcohols oxidation occurs through a first step where adsorbed molecules on the oxide surface decompose in alkoxy groups (RO ads ) after hydrogen extraction [2,12,13,18]. These surface species react with adsorbed oxygen (for example O ads − ) to give CO 2 as follows:…”
Section: Sensing Testsmentioning
confidence: 93%